VOZES SOCIAIS EM RELATÓRIOS DE ESTÁGIO SUPERVISIONADO DE LÍNGUA INGLESA E A CONSTITUIÇÃO DA IDENTIDADE DOCENTE - WENG, ANA KELLEN RIBEIRO (2023)
This research, situated in the field of Applied Linguistics, aims to understand the movement of resonating social voices in internship reports, in order to verify how they contribute to the construction of teaching identity. The specific objectives are to analyze the resonating voices of internship experiences in excerpts of reports using the theoretical and methodological assumptions of dialogism, and to analyze the construction of teaching identity underlying the voices that echo in these documents. The reports under analysis were produced by the researcher herself, occupying the position of student teacher (ST) in the Supervised Internship (SI) discipline in English Language, in the English Letters course of a public university in the Central-Southern region of the state of Paraná, Brazil, from 2019 to 2021, encompassing the pandemic period. This is a self-reflective study, as the researcher seeks to analyze her own accounts of her own praxis, aiming to highlight the voices that may permeate such records in order to indicate her identity constitution as a teacher in the context of SI. For this purpose, this investigation is based on the assumptions of Dialogism from the Bakhtin Circle, specifically the concept of social voices (MEDVIÉDEV, 2016 [1928]; VOLÓCHINOV, 2019[1926]; 2021[1929]; BAKHTIN (2011[1979]; 2014). The research methodology is qualitative and documentary, since the research corpus consists of internship reports corresponding to phases I and II of this discipline. Through this study, we were able to highlight the diverse social voices that permeate the ST's reports, echoing from her initial formation. We emphasize here that voices are ideological threads that traverse individuals, composing their concrete utterances. Thus, we understand that the constitution of the ST's teaching identity occurred dialectically and dialogically in the interaction of various voices, including those of the supervising and cooperating teachers, fellow student-teachers, students, as well as academic-scientific voices – the theorists – fostering voices that challenge traditional teaching and learning approaches, moving towards dialogicity, resonating with her life as a student-teacher-researcher, particularly in school and academic environments, laden with tensions and ideologies from her daily experiences. We further understand that identity, as a movable celebration (HALL, 2006), is not static but constituted through the conflicting movement of social relations mediated by language. With our study, we hope to stimulate new discussions, considering the relevance of reflection on praxis in order to strengthen initial teacher education.